Vapour sensitivity of an ALD hierarchical photonic structure inspired by Morpho. (9th May 2016) - Poncelet, Olivier; Tallier, Guillaume; Mouchet, Sébastien R; Crahay, André; Rasson, Jonathan; Kotipalli, Ratan; Deparis, Olivier; Francis, Laurent A
Abstract: The unique architecture of iridescent Morpho butterfly scales is known to exhibit different optical responses to various vapours. However, the mechanism behind this phenomenon is not fully quantitatively understood. This work reports on process developments in the micro-fabrication of a Morpho -inspired photonic structure in atomic layer deposited (ALD) materials in order to investigate the vapour optical sensitivity of such artificial nanostructures. By developing recipes for dry and wet etching of ALD oxides, we micro-fabricated two structures: one combining Al2 O3 and TiO2, and the other combining Al2 O3 and HfO2 . For the first time, we report the optical response of such ALD Morpho -like structures measured under a controlled flow of either ethanol or isopropyl alcohol (IPA) vapour. In spite of the small magnitude of the effect, the results show a selective vapour response (depending on the materials used).